PROVIDING SCIENCE-DEVELOPMENT INTEGRATION PLACE OF TECHNOPARKS - Shakirova Farogat Boltaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
In a modern economy, the creation of innovations and their introduction into production is one of the main factors of national competitiveness. The disconnect between science and production slows down innovative development. Therefore, technoparks are of great importance as the main infrastructure connecting these two sectors. Technopark is an innovative area that unites research institutes, higher education institutions, startups and manufacturing enterprises, and performs the following tasks: commercialization of scientific research results; creation of a laboratory and incubation environment for students and researchers; support for startups; implementation of scientific solutions for enterprises; transfer of modern technologies to the local economy. For this process to be effective, special infrastructure - technoparks - is very important. Today, it is important to study the world experience of technoparks and study the issues of their implementation in practice.